2002
DOI: 10.1021/bc025536j
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin B-Labile Dipeptide Linkers for Lysosomal Release of Doxorubicin from Internalizing Immunoconjugates:  Model Studies of Enzymatic Drug Release and Antigen-Specific In Vitro Anticancer Activity

Abstract: The anticancer drug doxorubicin (DOX) has been linked to chimeric BR96, an internalizing monoclonal antibody that binds to a Lewis(y)-related, tumor-associated antigen, through two lysosomally cleavable dipeptides, Phe-Lys and Val-Cit, giving immunoconjugates 72 and 73. A self-immolative p-aminobenzyloxycarbonyl (PABC) spacer between the dipeptides and the DOX was required for rapid and quantitative generation of free drug. DOX release from model substrate Z-Phe-Lys-PABC-DOX 49 was 30-fold faster than from Z-V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
403
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 460 publications
(451 citation statements)
references
References 23 publications
10
403
0
1
Order By: Relevance
“…We showed that PEG-vcTNF-α was cleaved by cysteine proteases, but not other proteases, to release TNF-α, and this release is dependent upon pH. Our finding that the valine-citrulline linker peptide is specifically targeted by cysteine proteases to release the peptide drug from the PEGylated conjugate is in agreement with previous reports [20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We showed that PEG-vcTNF-α was cleaved by cysteine proteases, but not other proteases, to release TNF-α, and this release is dependent upon pH. Our finding that the valine-citrulline linker peptide is specifically targeted by cysteine proteases to release the peptide drug from the PEGylated conjugate is in agreement with previous reports [20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 82%
“…Previous reports have demonstrated the success of conjugating a cytotoxic agent to a tumor-selective monoclonal antibody (mAb) using a protease-sensitive dipeptide linker. These antibody-drug conjugates include cBR96-valine-citrulline-MMAE and BR96-valine-citrulline-DOX (specific to Lewis Y antigen on carcinomas), cAC10-valine-citrulline-MMAE (specific to CD30 on hematological malignancies), and huPr1-valine-citrulline-MMAE (specific to hormone-resistant prostate cancer), and have high stability in plasma and efficient release of drug in tumor tissues [20][21][22][23][24][25].…”
mentioning
confidence: 99%
“…The removal of the acetazolamide moiety from the linker-payload combinations abrogated therapeutic activity in all experimental systems, confirming that the ligand-based delivery of cytotoxic drugs to the extracellular tumor environment represents a strict requirement for anticancer efficacy. Both compounds 4a and 5a described in this article feature a linker containing a valine-citrulline moiety, which was previously believed to be particularly suited for the intracellular release of drug payloads, due to the action of lysosomal cathepsin B [41]. This protein is a primarily intracellular protease that can be secreted extracellularly by dying cells, but also by living tumor cells to initiate extracellular proteolytic cascades and to enable tumor cell proliferation [42].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally we explored antibody-drug conjugates (ADCs) as a therapeutic modality for the selective targeting of CD133-expressing tumours. Recent advances with ADCs using peptide linkers showed enhanced efficacy and better specificity to antigen-expressing cells (Dubowchik et al, 2002;Doronina et al, 2003Doronina et al, , 2006. Specifically, an anti-human CD133 monoclonal antibody (MAb), AC133, was directly conjugated to the potent cytotoxic drug, monomethyl auristatin F (MMAF) , using a valine-citrulline dipeptide linker that is cleavable by proteases (Doronina et al, 2003).…”
mentioning
confidence: 99%